PANDANGAN DUNIA DEWI ANGGRAENI DALAM NOVEL MY PAIN MY COUNTRY: KAJIAN STRUKTURALISME GENETIK LUCIEN GOLDMANN (DEWI ANGGRAENI’S WORLD VIEW IN MY PAIN MY COUNTRY: LUCIEN GOLDMANN GENETIC STRUCTURALISM STUDY) - Derri Ris Riana (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2021)
Abstract Dewi Anggraeni’s World View in My Pain My Country: Lucien Goldmann Genetic Structuralism Study. This research aims to uncover human facts, collective subject, the structure of the novel My Pain My Country, which illustrates the character's problems, both concerning other characters and the environment, and the worldview expressed by the author as part of a social class group supported by Dewi Anggraeni's authorship helped to reconstruct the author's worldview. The analysis uses genetic structuralism with a dialectical method based on the concept of understanding and explanation in finding coherence of meaning. The data source is Dewi Anggraeni’s novel ”My Pain My Country”. The results showed that the author described “My Pain My Country” as human facts through geographical, sociological, psychological, historical, and ideological facts. Dewi Anggraeni describes the collective subject in two different social classes, namely the Chinese ethnic group to be described as the capitalists and indigenous people as the proletarians. The structure of “My Pain My Country” was constructed by relating the characters and the environment. The author represented the relationship between the characters in human opposition. Meanwhile, the relationship between the characters and the environment were represented through natural, social and cultural oppositions. The structure of the novel reflected the Dewi Anggraeni’s worldview as a form of sympathy, not only towards the victims of the 1998 tragedy from Chinese but also towards the lower middle class of indigenous people; and world views on nationalism, justice, and Chinese integration. Key words: genetic structuralism, human fact, world view Abstrak Pandangan Dunia Dewi Anggraeni dalam Novel My Pain My Country: Kajian Strukturalisme Genetik Lucien Goldmann. Penelitian ini bertujuan untuk mengungkap fakta kemanusiaan; subjek kolektif; struktur novel My Pain My Country yang menggambarkan permasalahan tokoh, baik dalam hubungannya dengan tokoh lain maupun dengan lingkungannya; dan pandangan dunia yang diekspresikan pengarang sebagai bagian dari kelas sosial yang didukung oleh jejak kepengarangan yang turut merekonstruksi pandangan dunia Dewi Anggraeni. Analisis menggunakan strukturalisme genetik dengan metode dialektik yang berdasarkan pada konsep pemahaman dan penjelasan dalam menemukan koherensi makna. Sumber data adalah novel My Pain My Country karya Dewi Anggraeni. Hasil penelitian menunjukkan bahwa novel My Pain My Country sebagai fakta kemanusiaan digambarkan pengarang melalui fakta geografis, sosiologis, psikologis, historis, dan ideologis. Subjek kolektif dimunculkan Dewi Anggraeni dalam dua kelas sosial yang berbeda, yaitu kelompok etnis Tionghoa yang digambarkan sebagai kaum kapitalis dan pribumi sebagai proletar. Struktur novel My Pain My Country dibangun oleh hubungan antartokoh, serta tokoh dan lingkungan. Hubungan tokoh dan tokoh digambarkan dalam oposisi manusia. Sementara itu, hubungan tokoh dan lingkungan digambarkan melalui oposisi alamiah, sosial, dan kultural. Struktur novel itu merefleksikan pandangan dunia Dewi Anggraeni sebagai wujud keprihatinan, baik terhadap korban tragedi 1998 dari Tionghoa maupun kelompok menengah ke bawah, serta pandangan tentang nasionalisme, keadilan, dan integrasi Tionghoa. Kata-kata kunci: strukturalisme genetik, fakta kemanusiaan, pandangan dunia